Prediction of chronic lung disease, survival and need for ECMO therapy in infants with congenital diaphragmatic hernia: additional value of fetal MRI measurements? - Schaible, Thomas; Büsing, Karen-Anett; Zahn, Katrin; Wessel, Lucas; Siemer, Jörn; Neff, Wolfgang (European journal of radiology, 2012)
Introduction: The lung-to-head ratio (LHR), measured by ultrasound, and the fetal lung volume (FLV), measured by MRI, are both used to predict survival and need for extra corporeal membrane oxygenation (ECMO) in infants with congenital diaphragmatic hernia (CDH). The aim of this study is to determine whether MRI measurements of the FLV, in addition to standard ultrasound measurements of the LHR, give better prediction of chronic lung disease, mortality by day 28 and need for ECMO. Materials and methods: Patients with unilateral isolated CDH born between January 2002 and December 2008 were eligible for inclusion. LHR and FLV were expressed as observed-to-expected values (O/E LHR and O/E FLV). Univariate and multivariate analyses were performed. Receiver operating characteristic curves were constructed and areas under the curve (AUC) were calculated to determine predictive values. Results: 90 patients were included in the analysis. Combined measurement of the O/E LHR and O/E FLV gave a slightly better prediction of chronic lung disease (AUC=0.83 and AUC=0.87) and need for ECMO therapy (AUC=0.77 and AUC=0.81) than standard ultrasound measurements of the O/E LHR alone. Combined measurement of the O/E LHR and O/E FLV did not improve prediction of early mortality (AUC=0.90) compared to measurement of the O/E LHR alone (AUC=0.89). An intrathoracal position of the liver was independently associated with a higher risk of early mortality (p<0.001), chronic lung disease (p=0.007) and need for ECMO therapy (p=0.001). Discussion: Chronic lung disease and need for ECMO therapy are slightly better predicted by combined measurement of the O/E LHR and the O/E FLV. Early mortality is very well predicted by measurement of the O/E LHR alone. Conclusion: Clinical relevance of additional MRI measurements may be debated.